Nature(s) at work - Sébastien Mouret; Nicolas Lainé (Revue d'anthropologie des connaissances)
This special issue of Revue d’Anthropologie des Connaissances offers a reflection on the development of diverse proposals and perspectives in the humanities and social sciences regarding the “work of nature”. This introduction provides a general but non-exhaustive overview of the notion of work in the knowledge production systems of animal and environmental studies. It firstly draws attention to the pioneering dimension of animal studies, as their seminal research called into question the Marxist legacy regarding the relation between work, subjectivity, and value. This subsequently gave rise to diverse reflections in the domains of the political economy and ethics. Secondly, this overview sheds light on the shifting boundaries of work in the environmental humanities to the realm beyond animals (i.e., microbes, plants, forest, biosphere). It brings to light the influence of animal studies as well as the characteristics and controversies of the approaches used in the environmental humanities to revise the separation between nature and work in response to the current ecological crisis. Finally, this overview shows how the tremendous interest in the notion of work in animal and environmental studies can help us to better understand and change our relationships with animals and nature.